Illness perceptions in adult congenital heart disease: A multi-center international study. (1st October 2017) - Rassart, Jessica; Apers, Silke; Kovacs, Adrienne H.; Moons, Philip; Thomet, Corina; Budts, Werner; Enomoto, Junko; Sluman, Maayke A.; Wang, Jou-Kou; Jackson, Jamie L.; Khairy, Paul; Cook, Stephen C.; et al.
Abstract: Background: Illness perceptions are cognitive frameworks that patients construct to make sense of their illness. Although the importance of these perceptions has been demonstrated in other chronic illness populations, few studies have focused on the illness perceptions of adults with congenital heart disease (CHD). This study examined (1) inter-country variation in illness perceptions, (2) associations between patient characteristics and illness perceptions, and (3) associations between illness perceptions and patient-reported outcomes. Methods: Our sample, taken from APPROACH-IS, consisted of 3258 adults with CHD from 15 different countries. Patients completed questionnaires on illness perceptions and patient-reported outcomes (i.e., quality of life, perceived health status, and symptoms of depression and anxiety). Patient characteristics included sex, age, marital status, educational level, employment status, CHD complexity, functional class, and ethnicity. Linear mixed models were applied. Results: The inter-country variation in illness perceptions was generally small, yet patients from different countries differed in the extent to which they perceived their illness as chronic and worried about their illness. Patient characteristics that were linked to illness perceptions were sex, age, employment status, CHD complexity, functional class, and ethnicity. Higher scores on consequences, identity, and emotional representation, as well as lower scores on illness coherence and personal and treatment control, were associated with poorer patient-reported outcomes. Conclusions: This study emphasizes that, in order to gain a deeper understanding of patients' functioning, health-care providers should focus not only on objective indicators of illness severity such as the complexity of the heart defect, but also on subjective illness experiences.